The cholinergic system in the olfactory center of the terrestrial slug Limax. Issue 13 (3rd April 2014) - Matsuo, Ryota; Kobayashi, Suguru; Wakiya, Kyoko; Yamagishi, Miki; Fukuoka, Masayuki; Ito, Etsuro
ABSTRACT Acetylcholine plays various important roles in the central nervous system of invertebrates as well as vertebrates. In the olfactory center of the terrestrial slug Limax, the local field potential (LFP) oscillates, and the change in its oscillatory frequency is thought to correlate with the detection of odor that potentially changes an ongoing behavior of the animal. Acetylcholine is known to upregulate the frequency of the LFP oscillation, and is one of the candidates for the neurotransmitters that are involved in such higher cognitive functions. However, there have been no histological data on the cholinergic system in gastropods, nor are there data on the receptors that are responsible for the upregulation of the oscillatory frequency of LFP due to the lack of analytical tools (such as antibodies or cDNA sequence information on cholinergic system‐related genes). Here we cloned the cDNAs of choline acetyltransferase (ChAT), acetylcholinesterase, vesicular acetylcholine transporter, and several nicotinic acetylcholine receptors (nAChRs), and investigated their localization in the brain of Limax. We also generated a polyclonal antibody against ChAT to examine its localization, and investigated pharmacologically the involvement of nAChRs in the LFP oscillation. Our data showed: 1) dense distribution of the neurons expressing mRNAs of ChAT and vesicular acetylcholine transporter in the olfactory center; 2) spatially unique expression patterns of different nAChRs in the olfactory center; 3) involvement of nAChRs in the upregulation of the oscillation; 4) localization of ChAT protein in nerve fibers and/or terminals; and 5) the presence of cholinergic nerves in the tentacles. J. Comp. Neurol. 522:2951–2966, 2014. © 2014 Wiley Periodicals, Inc.